Numerical wave simulation for interactive audio-visual applications - Raghuvanshi, Nikunj; Allen, Andrew; Snyder, John (Journal of the Acoustical Society of America, 2016)
Sound is an integral part of many interactive applications, such as 3D computer games. The generality and complexity of the simulated domains makes wave simulation a natural fit. The opposing goals of real-time execution and compute intensiveness of wave simulation provide a rich ground for designing novel computational methods. Two instances of such audio-visual interactive techniques will be discussed. The first technique employs precomputed wave simulation for providing acoustic effects in computer games. Time-domain 3D simulation is performed from many prospective player positions, resulting in a 7D field containing billions of acoustic responses. Perceptual encoding is then performed to drastically reduce memory requirements. Interactive motion of player and sources in the game can then be accommodated via quickly decoding and auralizing the pre-calculated waveeffects. The second technique explores the limits of real-time parallel numerical acoustic computation on today's desktop graphics cards. The user is presented with a 2D “sandbox” environment for designing virtual 2D musical wind instruments that are instantly simulated in real-time for the entire human auditory bandwidth. Instrument shape editing and performance via manipulating tone-holes/valves can be done on-the-fly. Video demonstrations of both techniques will be shown along with a discussion of the core technical ideas.